Coping With Dynamism: Phylogenetics and Phylogeographic Analyses Reveal Cryptic Diversity in Heleobia Snails of Atacama Saltpan, Chile - Valladares, Moisés A.; Fabres, Alejandra A.; Collado, Gonzalo A.; Sáez, Paola A.; Méndez, Marco A. (Frontiers in Ecology and Evolution, 2022)
The species that inhabit systems highly affected by anthropic activities usually exhibit this external influence in their gene pool. In this study, we investigated the genetic patterns of populations of Heleobia atacamensis, a freshwater microgastropod endemic to the Atacama Saltpan, a system historically exposed to environmental changes, and currently subjected to conditions associated with metallic and nonmetallic mining and other anthropic activities. Molecular analyses based on nuclear and mitochondrial sequences indicate that the saltpan populations are highly fragmented and that the genetic structure is mainly explained by historical geographic isolation, with little influence of contemporary factors. The microsatellite results suggest a moderate genetic diversity and sharp differentiation mediated by isolation by distance. Additionally, despite the high environmental heterogeneity detected and the marked historical dynamism of the region, our data reveal no signs of demographic instability. The patterns of contemporary gene flow suggest a change in the current genetic structure, based on the geographic proximity and specific environmental conditions for each population. Our results, highlight the role of fragmentation as a modulator of genetic diversity, but also suggest that the historical persistence of isolated populations in naturally dynamic environments could explain the apparent demographic stability detected.